A Novel Bacterium, Butyricimonas virosa, Preventing HFD-Induced Diabetes and Metabolic Disorders in Mice via GLP-1 Receptor - Lee, Heetae; An, Jinho; Kim, Jiyeon; Choi, Dohyun; Song, Youngcheon; Lee, Chong-Kil; Kong, Hyunseok; Kim, Sang Bum; Kim, Kyungjae (Frontiers in Microbiology, 2022)
Knowledge of the impact of the gut microbiota on human health has increased, and modulation of the bacterial community is now considered a therapeutic target for various diseases. Certain novel bacterial species have probiotic properties associated with improvement in obesity and related metabolic disorders. The relative abundance of Butyricimonas spp. is correlated with metabolic parameters; however, the physiological role of Butyricimonas in metabolic improvement is unclear. In this study, live and heat-killed Butyricimonas virosa were administered to mice with high-fat diet (HFD)-induced obesity. Both live and heat-killed B. virosa ameliorated HFD-impaired body weight, serum glucose level, insulin resistance, and liver steatosis. Moreover, activation of the glucagon-like peptide-1 receptor (GLP-1R) and peroxisome proliferator-activated receptor  (PPAR) was observed in the liver, and the expression levels of insulin receptor substrate (IRS)-1, IRS-2, Toll-like receptor 5 (TLR5), and zonula occludens-1 (ZO-1) were upregulated in the ileum. Finally, we demonstrated that the effect of B. virosa treatment on glucose regulation may be linked to the upregulation of GLP-1R in the liver, and is not a result of colonization of the gut by B. virosa or B. virosa-produced butyrate. Our results provide a rationale for the development of Butyricimonas spp.-based therapeutics and prophylactics for hyperglycemia.